The Influence of Gojek Slogan Towards Brand Image, Brand Awareness, and Brand Loyalty - Avmeilputra, Muhammad Hashfi; Hudrasyah, Herry (Journal of Business and Management, 2020)
Abstract. The increasingly competitive market conditions make consumers have many choices for the products they want. Therefore, building brand loyalty becomes more essential. Some factors that influence brand loyalty are brand awareness and brand image. One of the ways to enhance brand awareness and brand image is by using slogan as a marketing strategy. Gojek is a brand that uses slogan as an essential element in their several marketing campaigns. In the market Gojek has a very tight competition with their competitor. One of the things that can differentiate them is how they  market their product. Because Gojek use slogan as their key strategy. Thus, the objective of this is to investigate the effectiveness of Gojek slogans as a marketing strategy on their brand image, brand awareness, and brand loyalty. To examine this, researcher conducted a quantitative survey method and collected data from 207 online participants who have used Gojek for 2 years, used 3 of Gojek services, have seen Gojek #PastiAdaJalan slogan, and aged 17-55 years old. Analysis conducted through the PLS-SEM approach indicates that the #PastiAdaJalan slogan has a significant direct effect on Gojek's brand image and brand awareness. However, the use of Gojek slogans does not have a direct influence  on brand loyalty. It has to go through mediating variables which are brand image and brand awareness.Outcomes from this research expected to give insights on the use of Gojek slogan towards building and enhancing brand image, brand awareness, and brand loyalty which provides recommendation for future research. Furthermore, the findings can be beneficial for Gojek to develop their strategy in using the slogan to compete better with their competitor.Keywords: Slogan, Brand Awareness, Brand Image, Brand Loyalty